Assessment of Corneal Densitometry in Rheumatoid Arthritis Patients - Mustafa Alpaslan Anayol; Başak Bostancı; Mehmet Ali Şekeroğlu; Mert Şimşek; Süleyman Günaydın; Pelin Yılmazbaş (Türk Oftalmoloji Dergisi, 2017)
Objectives: To evaluate corneal densitometry and anterior segment parameters of rheumatoid arthritis (RA) patients and compare these results with those of age-matched healthy control subjects. Materials and Methods: Anterior segment parameters and corneal densitometry of patients with RA and healthy control subjects were assessed by Scheimpflug corneal topography. For densitometry analysis, the 12-mm diameter area of the cornea was subdivided into four concentric radial zones and anterior, central, and posterior layers based on corneal depth. Right eyes of subjects were used for statistical analysis. Results: Twenty-three consecutive patients with RA and 22 healthy control subjects were included in the study. There was no significant difference with regard to age (p=0.487) or gender (p=0.514). When anterior segment parameters of both groups were compared, no significant difference was found (p>0.05). Total corneal densitometry values were statistically higher in the RA group (p=0.030). In addition, when subdivisions of the cornea were evaluated, higher densitometry values were found in the RA group in 0-2 and 2-6 mm radial zones both in the anterior and total depth (p=0.001, p=0.003 for the 0-2 mm zone and p=0.002, p=0.009 for the 2-6 mm zone). Corneal densitometry measurement was not correlated with central corneal thickness or simulated keratometry value in RA patients or healthy control subjects. Conclusion: The corneal densitometry values were higher in RA patients when compared to healthy control subjects, even if they had clinically clear corneas. Corneal densitometry as an objective measure of corneal clarity warrants further studies in order to ascertain its clinical relevance in RA patients.